The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4314/ovj.v7i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Schmallenberg virus and other Simbu group viruses among the Lebanese sheep

Abstract: In order to evaluate for the first time, the serological prevalence of Schmallenberg virus (SBV) and other Simbu group viruses in Lebanon, sheep originating from 15 Lebanese regions were sampled in September 2016. A total number of 750 serum samples from Awassi sheep were tested by ELISA for viral nucleoprotein antibodies. From the sampled animals, 122 animals were seropositive to SBV/Simbu group viruses. The seropositive sheep were mainly located in South Lebanon. At herd-level, a seroprevalence of 53.33% was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The average seroprevalence of 24.5% in Belgrade for the period 2017-2022 is higher than estimated by Bojkovski et al ( 2015) [16] who reported the seroprevalence of 13.45% for the Republic of Serbia in previous years but in agreement with the results provided for Vojvodina where the seroprevalence of SD in sheep was 22% in the period 2013-2018 [6]. A similar seroprevalence was reported in other countries such as Poland [17], Switzerland [18], Lebanon [19], and Spain [20]. The results are consistent with the results of SB seroprevalence in Kosovo in sheep (19.2%) in 2014 and 2016.…”
Section: Discussionsupporting
confidence: 86%
“…The average seroprevalence of 24.5% in Belgrade for the period 2017-2022 is higher than estimated by Bojkovski et al ( 2015) [16] who reported the seroprevalence of 13.45% for the Republic of Serbia in previous years but in agreement with the results provided for Vojvodina where the seroprevalence of SD in sheep was 22% in the period 2013-2018 [6]. A similar seroprevalence was reported in other countries such as Poland [17], Switzerland [18], Lebanon [19], and Spain [20]. The results are consistent with the results of SB seroprevalence in Kosovo in sheep (19.2%) in 2014 and 2016.…”
Section: Discussionsupporting
confidence: 86%
“…A model for the transmission of SBV between regions in Europe suggested that vector dispersal is the principal mechanism for transmission of SBV, even at the continental scale [219]. More recently, SBV has been reported in countries outside of Europe, including Azerbaijan [31], China [32], Ethiopia [33, 34], Iran [35], Lebanon [36], Namibia [38] and Mozambique [31, 37] suggesting possible geographical expansion of SBV. However, reports of SBV emergence in new geographical regions which are based solely on serological detection of SBV antibodies, particularly when samples originate in regions where other Simbu viruses are known to be enzootic, should be interpreted cautiously as some ELISAs can have cross-reactivity between SBV and other Simbu viruses [114].…”
Section: Introductionmentioning
confidence: 99%